Sustainable innovation with a method based on peripheral mononuclear cells to screen, monitor and stratify the population at risk of osteoporosis and fractures – a multicenter cross-sectional trial protocol - Salamanna, Francesca; Brogini, Silvia; Di Martino, Alberto; Baldini, Nicola; Gaudio, Agostino; Castellino, Pietro; Contartese, Deyanira; Di Censo, Chiara; Giavaresi, Gianluca; Faldini, Cesare; Fini, Milena (Frontiers in Endocrinology, 2025)
IntroductionOsteoporosis (OP) is a growing global public health challenge, often underdiagnosed and underestimated due to limitations in current diagnostic tools such as DXA-based bone mineral density (BMD) assessment and FRAX score. These methods do not fully capture fracture risk nor account for gender-specific and metabolic differences. A novel patented diagnostic method, based on the in vitro behavior of peripheral mononuclear cells (PBMCs) may offer a more accessible, dynamic, and biologically representative approach to OP diagnosis and stratification.Methods and analysisThis multicenter, double-blind, cross-sectional clinical trial protocol aims to evaluate the diagnostic potential of the PBMC-based test using blood samples (2–5 mL) from 120 participants stratified by BMD (healthy, osteopenic, osteoporotic fractured and non-fractured). PBMCs are isolated and cultured in vitro to assess viability, number, size, and spontaneous osteoclast differentiation over time. Additionally, blood samples are analyzed for T lymphocyte subpopulations, pro- and anti-inflammatory cytokines, platelet-related parameters, and markers of bone turnover. All outcomes are analyzed considering gender differences. Correlation and accuracy analyses will determine the relationship between cellular and biochemical markers and OP status.Ethics and disseminationThe study protocol has been approved by Emilia Romagna’s Ethics Committee (CE-AVEC), Bologna, Italy. Written informed consent is obtained from all participants. Findings of this study will be disseminated through peer-reviewed publications and conference presentations.Clinical Trial Registrationhttps://clinicaltrials.gov/, identifier NCT06551155.